CIVIL SOCIETY AND INTERNATIONAL ORGANIZATIONS IMPACT ON GENDER POLICY IN UKRAINE - Біденко, Ю. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article analyzes the development of gender policy in Ukraine taking in the context ofinternational commitments and incentives, as well as the participation of civil society. It is shownthat while civil society organizations are rather active in updating and implementing genderprojects, unlike political parties and media, they do not have regulated instruments for influencingpublic policy that is not consistent or prioritize the issues of gender balance achievement.